A hybrid circular economy - Game theoretical approach in a dual-channel green supply chain considering sale's effort, delivery time, and hybrid remanufacturing. (20th March 2020) - Alizadeh-Basban, Nima; Taleizadeh, Ata Allah
Abstract: The circular economy (CE) and the marketing activities are the key subjects to attract the market share in today's complex supply chain. Here, dual selling channels, the online delivery time, and the distributor sales effort are considered as marketing activities to attract the customers. Moreover, in order to meets the economic and environmental principles of the CE, three responsibilities to ease the carbon emission, as approaches for the return on investment, are devised, including investment in the green production, the cap and trade regulation, and the hybrid remanufacturing via both the manufacturer and the distributor under the technology license. This such complex supply chain needs to determine the equilibrium amounts of the distinguishing elements, including the pricing strategy, remanufacturing approaches, delivery time, and sales effort to abate the conflicts between the members, and consequently, to enhance the economic and CE objectives of the supply chain (SC). In order to obtain the equilibrium decision makings, three game theoretical approaches, including the manufacturer-Stackelberg game (SM), the distributor-Stackelberg game (SR) and the Nash game (N) are employed. The interaction between the game sequences and the remanufacturing process is the key purpose of this paper to not only maximize the profit of SC but also to enrich the CE and marketing goals of this research. The outcomes presented that the SM game, where the manufacturer remanufactures most of the defected products which are collected via the distributor, is the best game strategy to improve the profits of both the distributor and the manufacturer, and also to enhance the other distinguishing elements. In addition, in the SR game, when most of the returns remanufacture via the distributor under the manufacturer license, it not only maximizes the profits of members but also lead to the improvement of the distinguishing elements. In the Nash game, however, there is a conflict between the members about the remanufacturing process, which reduces the SC profit in this game as compared to other ones.